Marketing and Distribution System Foster Misuse of Antibiotics in the Community: Insights from Drugs Wholesalers in India - Anita Kotwani; Arti Bhanot; Girdhari Lal Singal; Sumanth Gandra (MDPI AG, 2022)
Antibiotic misuse is one of the major drivers of antimicrobial resistance (AMR). In India, evidence of antibiotic misuse comes largely from retailers as well as formal and informal healthcare providers (IHCPs). This paper presents the practices and perspectives of drug wholesalers, a critical link between manufacturers and last-mile dispensers. Four experienced wholesalers and an ex-State Drug Controller (ex-SDC) were interviewed in depth, using semi-structured guides in the National Capital Region of Delhi, India, between November 2020 and January 2021. Four main findings were that wholesalers (i) have limited knowledge about wholesale licensing and practice regulations, as well as a limited understanding of AMR; (ii) directly supply and sell antibiotics to IHCPs; (iii) facilitate medical representatives (MRs) of pharmaceutical companies and manufacturers in their strategies to promote antibiotics use in the community; and (iv) blame other stakeholders for unlawful sale and overuse of antibiotics. Some of the potential solutions aimed at wholesalers include having a minimum education qualification for licensing and mandatory Good Distribution Practices certification programs. Decoupling incentives by pharmaceutical companies from sales targets to improve ethical sales practices for MRs and optimize antibiotic use by IHCPs could alleviate wholesalers' indirect actions in promoting antibiotic misuse.